Phytochemical analysis, antioxidant, α‑glucosidase inhibitory activity, and toxicity evaluation of Orthosiphon stamineus leaf extract - Ahda, Mustofa; Jaswir, Irwandi; Khatib, Alfi; Ahmed, Qamar Uddin; Mahfudh, Nurkhasanah; Ardini, Yunita Dewi; Syed Mohamad, Sharifah Nurul Akilah; Anwar, Muslih; Hernawan, Hernawan; Miyashita, Kazuo; Salamatullah, Ahmad Mohammad (Springer Nature, 2023)
Ocimum aristatum, commonly known as O. stamineus, has been widely studied for its potential as an herbal medicine candidate. This research aims to compare the efcacy of water and 100% ethanolic extracts of O. stamineus as α-glucosidase inhibitors and antioxidants, as well as toxicity against zebrafsh embryos. Based on the study fndings, water extract of O. stamineus leaves exhibited superior inhibition activity against α-glucosidase, ABTS, and DPPH, with IC50 values of approximately 43.623 ± 0.039 µg/mL, 27.556 ± 0.125 µg/mL, and 95.047 ± 1.587 µg/mL, respectively. The major active compounds identifed in the extract include fatty acid groups and their derivates such as linoleic acid, α-eleostearic acid, stearic acid, oleanolic acid, and corchorifatty acid F. Phenolic groups such as cafeic acid, rosmarinic acid, 3,4-Dihydroxybenzaldehyde, norfenefrine, caftaric acid, and 2-hydroxyphenylalanine and favonoids and their derivates including 5,7-Dihydroxychromone, 5,7-Dihydroxy-2,6-dimethyl-4H-chromen-4-one, eupatorin, and others were also identifed in the extract. Carboxylic acid groups and triterpenoids such as azelaic acid and asiatic acid were also present. This study found that the water extract of O. stamineus is non-toxic to zebrafsh embryos and does not afect the development of zebrafsh larvae at concentrations lower than 500 µg/mL. These fndings highlight the potential of the water extract of O. stamineus as a valuable herbal medicine candidate, particularly for its potent α-glucosidase inhibition and antioxidant properties, and afrm its safety in zebrafsh embryos at tested concentrations.